Thiel embalming: Quantifying histological changes in skeletal muscle and tendon and investigating the role of boric acid. Issue 5 (23rd October 2019) - McDougall, Seaneen; Soames, Roger; Felts, Paul
Abstract : Cadaver preservation methods impact their utilization in anatomical research and teaching. Thiel‐embalmed cadavers show flexibility, however, the cause remains poorly understood. This study aimed to (1) describe qualitative and quantitative histological differences between Thiel‐embalmed and formalin‐fixed skeletal muscle and tendon tissue; (2) investigate whether boric acid in Thiel solution is solely responsible for modification of tissues; and (3) explore whether the modifications observed could potentially explain the mechanisms underpinning flexibility of Thiel cadavers. Skeletal muscle and tendon samples were harvested from mice preserved using formalin, Thiel solution, or modified‐Thiel solution (without boric acid). Using standard H&E and Gomori's trichrome histological methods, tissues were examined to determine whether differences were apparent between the preservative treatments. Differences were present between the Thiel and formalin‐fixed tissues; formalin‐fixed samples remained substantially more intact while Thiel‐embalmed samples showed fiber fragmentation and lack of nuclei. The mean cell diameter of Thiel‐embalmed muscle (24.4 μm) was significantly smaller ( P < 0.005) than formalin‐fixed muscle (40.7 μm). There was significantly greater ( P < 0.005) fragmentation in Thiel‐embalmed muscle (631.5 per 1 mm 2 ) compared to formalin‐fixed muscle (75.4 per 1 mm 2 ). Samples embalmed using modified‐Thiel showed a severe lack of integrity within internal tissue structure. This suggests that Thiel solution significantly alters tissue structure at cellular level, with quantitative data demonstrating measurable differences between Thiel and formalin‐fixed specimens. While the precise mechanism for these alterations remains unknown, it is shown that boric acid is not the only component of Thiel responsible for degradation of internal tissue structure. Clin. Anat., 33:696–704, 2020. © 2019 Wiley Periodicals, Inc.